Modelos híbridos de segurança - Nogueira, Pedro Miguel Ferreira da Silva (2017)
Globalization has increased the proximity between people, organizations and states, intensifying relations and change processes. In this context, awareness of the end of invulnerability illusion and of the structural nature of security, is assumed as one of the most striking features of modernity. The state, as a collective logic dependent on the historical context, has been able to adapt itself to reconfigured management models and tools, where freedom and security go hand in hand, following a sort of dynamic balance, increasingly centered on the citizen. In this framework, the redefinition of public and private security space has evolved to integrate new fields, actors, objects and instruments, seeking, although not always in a clear and obvious manner, to create value in terms of results, service quality and citizen confidence. This research sought to point out ways for the State to enhance partnership between the public and private security sector, adopting a qualitative research strategy, accomplished through desk research and a semi-structured interview survey, whose data was object of content analysis, seeking to contribute to a comprehensive approach to the phenomenon of (in)security, in an interdisciplinary and complex perspective. The private security activity, with a law enforcement subsidiary and complementary role, has grown to the necessary extent, being known for a number of weaknesses that, associated with the risk of "vigilantism" and Security State building, influence the development of a public and private partnership concept. The development of the security sector, especially in its private dimension, tends to promote a kind of "security bubbles", in which the State should face the challenging task and responsibility of leading the process of integration and profitability for structures, human and material resources, decisive to meet the current requirements of effectiveness and efficiency for people’s security and safety. The role of citizens, municipalities and local partnerships, along with the need to reconfigure “moonlighting” and “commercialized” police services and ensure an effective regulation, supervision and control of private security company activities based on a co-production concept, configures current challenges that can and must contribute to achieve more and better security. In this sense, it is assumed that, despite the ongoing renewal of obstacles to the security sector and the inherent need to enable appropriate responses, the starting and finishing point must necessarily be maintained: we all equally have a right to security and safety!